The North Side Children's Agency (B) : finances versus mission - Donnelly, Anne Cohn, (SAGE knowledge. Cases., 2016)
The North Side Children's Agency (NSCA) was a nonprofit founded to serve low-income working parents who qualified for income-based government child care subsidies. In support of its mission, the NSCA operated year-round, full-day child care programmes. After years of success, in 2004 the NSCA faced a serious cash shortage and its first deficit in a decade. This case explains how the board members faced up to the issue.